Daâ€™wah Bil hal: A Study of Muhammadiyah’s Social Movements in Wolo During the Political Dynamics of the Old and New Order Eras - Alifuddin, Muhammad; Rosmini, Rosmini; Iye, Risman (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
ABSTRACT This study aims to understand how Muhammadiyah in Wolo Kolaka implements da’wah bil hal (practical preaching) through its social movements and how these movements respond to the repressive and authoritarian political situation of that time. This study uses a descriptive-analytical method, incorporating observation, documentation, and interview techniques. The results show that Muhammadiyah in Wolo Kolaka demonstrates a strong commitment to spreading Islamic values and assisting the community through various social activities amidst complex political dynamics. Despite facing a closed political space and various obstacles, Muhammadiyah in Wolo Kolaka has managed to adapt and continue its social movements through careful strategies. They focus on non-controversial activities, build relationships with the government, maintain political neutrality, and shift the focus of their preaching towards community empowerment. The impact of Muhammadiyah's social movement in Wolo Kolaka may not be as rapid and significant as in more open eras. However, their contributions in the fields of education, health, and community empowerment at the local level remain significant. Their careful preaching strategy and focus on empowerment can have a long-term impact on building a more independent, critical, and Islamically-rooted society. Muhammadiyah's experience in Wolo Kolaka provides important lessons on the importance of adaptive and sustainable strategies in facing limited political spaces, as well as the significance of da’wah bil hal in creating a prosperous and faithful society.